Cirugía de revascularización miocárdica en un paciente con Situs Inversus Totalis: Reporte de un caso - Espinoza-Romero, Cristhian (2021)
Dextrocardia with situs inversus totalis is a rare congenital abnormality. Most coronary artery bypass grafting surgeries in patients with dextrocardia were performed with anastomosis, using the right internal thoracic artery to revascularize the left anterior descending. It should be noted that in the literature there are few reports of coronary artery bypass grafting surgery, in a patient with this abnormality, its anatomical complexity constitutes a challenge in planning the surgical technique and the grafts to be used. We present an unusual case of a patient with situs inversus totalis and coronary artery disease who underwent coronary artery bypass grafting surgery making it a more technically complex procedure for surgeons, in addition to the difficulty in choosing grafts.